Factors Influencing Job Performance among Academic Staff in Malaysian Public University - Che Mohd Syaharuddin Che Cob; Ummi Kalsom Zakaria; Mohd Hafeez Al-Amin Abdul Wahab; Julaina Baistaman; Siti Nur Zahirah Omar; Nor Baizura Osman (Information Management and Business Review, 2024)
Extensive research has been conducted on the factors that determine job performance. The current study was required by a lack of research relating to the factors of job performance among academic staff in Malaysian public universities. The purpose of this study is to investigate the effects of personality traits, motivation, leadership style, and learner autonomy on job performance. Data was collected from the academic staff of a public university in Malaysia. The probability technique, which is simple random sampling was used in this study. The study is guided by an adapted ten-point Likert Interval Scale structured questionnaire as the main instrument used in collecting the data. Furthermore, the analysis of data was undertaken by using Confirmatory Factor Analysis (CFA) procedures. Structural equation modeling (SEM), a multivariate approach, was used to empirically evaluate and estimate the hypothesized link between constructs using Analysis of Moment Structure (AMOS) software version 20.0. The findings indicate that job performance is significantly and positively related to personality traits, motivation, leadership style, and learner autonomy. Motivation is a significant predictor of job performance when compared to other variables. The study proves that the combination of personality traits, motivation, learner autonomy, and leadership style on job performance may contribute to the optimal service delivery to stakeholders within Malaysia's educational system. Therefore, the implications of the findings, potential limitations, and directions for future research are also discussed